Online News Media Coverage of Sea Turtles and Their Conservation. (10th February 2021) - Santos, Bianca S; Crowder, Larry B
ABSTRACT: The media can be key in informing individuals around topics not easily observable, such as remote environmental issues and wildlife. Sea turtles are enigmatic animals that attract public attention, but they have faced severe population declines worldwide. Assessing how the news reports on sea turtle conservation is critical in evaluating how a concerned layperson may perceive threats affecting these animals and can provide insights on how experts can better engage with the media. We collected online articles about sea turtles from 2003 to 2019, recording the frequency by which various threats were mentioned as hazardous to sea turtles, the types of solutions noted in response to these threats, and common quoted messengers. We found that the media disproportionately reports on the threats of pollution and resource use. Importantly, this may not align with scientific consensus of top conservation concerns for these animals and can be problematic if it leads to a misinformed public.